2017
DOI: 10.1007/s00784-017-2280-2
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between ENAM gene polymorphism and dental caries in primary and permanent teeth in Czech children

Abstract: Although ENAM is considered as a candidate gene for dental caries, the presence of the ENAM variant (rs12640848) cannot be used as a risk factor of this multifactorial disease in the Czech population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
1
20
1
Order By: Relevance
“…Also, one study [23] reported an elevated risk of ENAM rs3796704 polymorphism and another study [5] showed an elevated risk of ENAM rs3796703 polymorphism in dental caries patients compared with controls. One research [21] reported that there were significant differences in the minor allele frequency between the Poles and Czechs populations. In addition, the sensitivity analysis confirmed the effect of ethnicity and type of control group on the association of ENAM rs3796704 and risk of dental caries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, one study [23] reported an elevated risk of ENAM rs3796704 polymorphism and another study [5] showed an elevated risk of ENAM rs3796703 polymorphism in dental caries patients compared with controls. One research [21] reported that there were significant differences in the minor allele frequency between the Poles and Czechs populations. In addition, the sensitivity analysis confirmed the effect of ethnicity and type of control group on the association of ENAM rs3796704 and risk of dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…The articles had been published from 2008 to 2019. Eleven studies had been conducted on Caucasians [12,[14][15][16][17][18][19][20][21][22][23], four studies had been conducted on Asians [5,13,24,25], and one on mixed [11] ethnicities.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Children were examined at the Ambulance of Pediatric Dentistry, University Hospital Brno, Czech Republic by an experienced pediatric dentist. The conditions of the clinical examination were published previously [14]. The decayed, missing, or filled teeth (d 3 mft) index was calculated using dental caries (d 3 level) as a cut-off point for the detection of decay.…”
Section: Clinical Data Collection and Samplingmentioning
confidence: 99%